2018
DOI: 10.1002/cnm.2971
|View full text |Cite
|
Sign up to set email alerts
|

Numerical research on the biomechanical behaviour of braided stents with different end shapes and stent‐oesophagus interaction

Abstract: Quasi-static and dynamic numerical analyses are carried out by referring to computational models of commercial self-expandable braided stents with 3 commonly used end shapes, to evaluate the influence of different end shapes of stent on the biomechanical interaction between stent and oesophagus. The end shape has no influence on the equivalent stress, but has a great influence on the contact stress in the narrowest zone of the oesophagus-neoplasm system. However, the end shapes have significant effect on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Much attention has been paid to the mechanical characteristics of the braided stent because of the stent's increasing clinical importance, and computational approaches have greatly contributed to clarifying apparent mechanical properties of the stent 18‐25 . Several numerical experiments that consider detailed mechanical characteristics of stent wires, such as the material nonlinearity 18,20,21,24 and three‐dimensional stress‐field, 21,22,25 have been conducted. This study also conducted a computational mechanical analysis of the braided stent; however, the motivation and aim of this study are different from those of existing computational studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Much attention has been paid to the mechanical characteristics of the braided stent because of the stent's increasing clinical importance, and computational approaches have greatly contributed to clarifying apparent mechanical properties of the stent 18‐25 . Several numerical experiments that consider detailed mechanical characteristics of stent wires, such as the material nonlinearity 18,20,21,24 and three‐dimensional stress‐field, 21,22,25 have been conducted. This study also conducted a computational mechanical analysis of the braided stent; however, the motivation and aim of this study are different from those of existing computational studies.…”
Section: Discussionmentioning
confidence: 99%
“…To remedy this issue, theoretical models of the braided stent have been proposed for estimating the radial forces of the braided stent for self‐expansion, in which the braided stent is modeled as an assembly of single helical springs 14‐17 . Numerical experiments using mechanically consistent computational models are also expected to be an effective alternative and several studies have attempted quantitative estimation of apparent mechanical characteristics of the braided stent 18‐29 . These numerical experiments considered material nonlinearities of stent wires (ie, superelasticity 18,20,21 and viscoelasticity 24 ), three‐dimensional (3‐D) mechanics within the wire cross‐sections through discretization of 3‐D volume meshes, 21 and structural design of the braided stent 19,22,23,25 and performed quantitative validations by conducting experiments and assessments of the stent mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 With the rapid development of computer technology, finite element analysis (FEA) technology has been widely used in cardiovascular disease researches due to its high efficiency and low cost. [11][12][13][14][15][16] Whitcher 17 adopted FEA to conduct fatigue analysis on the nitinol stent and highlighted that the simulation results were in good agreement with in vitro experiment. Auricchio et al, 18 by simulating the fatigue resistance of stents under cyclic bending and pulsation pressure loads, found that stents were more likely to become invalid under cyclic bending loads.…”
Section: Introductionmentioning
confidence: 99%